The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/aem.01207-16
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Proteomic Responses of Continuous Cultures of Microcystis aeruginosa PCC 7806 to Changes in Iron Bioavailability and Growth Rate

Abstract: The hepatotoxin microcystin (MCYST) is produced by a variety of freshwater cyanobacterial species, including Microcystis aeruginosa. Interestingly, MCYST-producing M. aeruginosa strains have been shown to outcompete their nontoxic counterparts under iron-limiting conditions. However, the reasons for this are unclear. Here we examined the proteomic response of M. aeruginosa PCC 7806 continuous cultures under different iron and growth regimes. Iron limitation was correlated with a global reduction in levels of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 64 publications
4
28
0
Order By: Relevance
“…Under oxidative stress, more MCs are released to the surrounding environment and therefore might play a role as a signal molecule to synchronize the cell responses to the stress-inducing agents. Increased intracellular MC concentration in response to oxidative stress conditions such as iron limitation support the hypothesis of MCs involvement in protection against oxidative stress, while the enhancement in extracellular MCs suggests the possible role of MCs as a signal molecule to make a better environmental adaptation (Yeung et al 2016).…”
Section: Future Outlook and Concluding Remarkmentioning
confidence: 58%
See 2 more Smart Citations
“…Under oxidative stress, more MCs are released to the surrounding environment and therefore might play a role as a signal molecule to synchronize the cell responses to the stress-inducing agents. Increased intracellular MC concentration in response to oxidative stress conditions such as iron limitation support the hypothesis of MCs involvement in protection against oxidative stress, while the enhancement in extracellular MCs suggests the possible role of MCs as a signal molecule to make a better environmental adaptation (Yeung et al 2016).…”
Section: Future Outlook and Concluding Remarkmentioning
confidence: 58%
“…A recent proteomic study using continuous cultures of M. aeruginosa PCC 7806 showed that under iron depletion physiological changes such as reduction in chlorophyll a content besides enhancement in MC production. Increased intracellular and extracellular MCs in continuous culture of M. aeruginosa PCC 7806 under iron depletion provided more evidence of the assistance role of MCs in the better fitness of Microcystis under oxidative stress conditions (Yeung et al 2016). In addition, mcy gene transcripts were enhanced under oxidative stress in various quantities i.e.…”
Section: Protection Against Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research raises the possibility that microcystins may play a role in enhancing the ability of surviving oxidative stress [1,31]. The increased production of intracellular MC under conditions of stress [32] allowed MC-producing strains to cope better with oxidative stress over non-toxic strain [21,30,33]. However, other findings show opposite results: The nontoxic M. aeruginosa PCC7806 mutant was favored over its toxic wild type when exposed to prolonged oxidative stress caused by hydrogen peroxide [34].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is deduced that the majority of MC–LR was kept inside the cells during our experiment and little MC–LR was released into external environment. Several studies have also reported that maximum MC concentrations were not recorded until the end of the growth cycle or during bloom collapse [ 73 ]. Therefore, iron addition could actually increase the intracellular toxin production but may not raise the extracellular MC–LR concentration during the blooms.…”
Section: Resultsmentioning
confidence: 99%